2004
DOI: 10.1016/j.chroma.2003.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Direct resistively heated column gas chromatography (Ultrafast module-GC) for high-speed analysis of essential oils of differing complexities

Abstract: This study applies Ultrafast module-GC (UFM-GC) with direct resistively heated columns to routine analysis of a group of essential oils of differing complexities (chamomile, peppermint, rosemary and sage). Essential oils were analysed by conventional GC with conventional inner diameter (i.d.) columns (0.25 mm) of different lengths (5 and 25 m long) and by Fast GC and Ultrafast module-GC with narrow bore columns (0.1 mm i.d., 5 m long). Column performance were evaluated and compared through their Grob test, sep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(29 citation statements)
references
References 14 publications
1
28
0
Order By: Relevance
“…The efficiency of the fast GC technique with a direct resistively heated column (ultra fast module-GC) was demonstrated for the analyses of various types of samples: essential oils, pesticides, lipids, etc. [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…The efficiency of the fast GC technique with a direct resistively heated column (ultra fast module-GC) was demonstrated for the analyses of various types of samples: essential oils, pesticides, lipids, etc. [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…The study was carried out by the chromato-massspectrometry method on an Agilent Technologies 6890 chromatograph with the mass-spectrometry detector 5973 [6,7]. The chromatography parameters: introduction of the sample (2 µl) in the chromatographic column was performed in the splitless mode.…”
Section: Methodsmentioning
confidence: 99%
“…Bicchi et al [30] applied ultrafast GC to the analysis of a series of essential oils by using resistively heated narrowbore columns. With respect to conventional GC applications, resolution was intentionally decreased but was maintained at a sufficient level for the separation of target compounds.…”
Section: Narrow-bore Columnsmentioning
confidence: 99%
“…The latter reports essential information relative to each application, which will not be repeated in this section (more details may be derived by directly consulting the reference). In the field of narrow-bore column fast GC research, a total of 18 essential oil applications are reported [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43]; Table 1 also reports the use of a short conventional column in fast GC essential oil analysis [9], while eight are focussed on fatty acid methyl ester (FAME) analysis [44][45][46][47][48][49][50][51]; single works regard triglycerides [52] and an alcoholic beverage [53]. More detailed information will be provided hereafter for some of the most representative high-speed GC examples.…”
Section: Narrow-bore Columnsmentioning
confidence: 99%